PENGARUH LINGKUNGAN KERJA, KOMUNIKASI, TUNJANGAN, DAN PENEMPATAN PEGAWAI TERHADAP SEMANGAT KERJA PEGAWAI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) BALITBANGTAN BENGKULU - Merta Kusuma; Ade Tiara Yulinda; Tezar Arianto (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Morale is believed to be something that influences success. So it is not surprising, if the organization demands it. In fact, work that is accompanied by work motivation tends to give better results. Therefore, this study seeks to examine matters related to work morale. The population were 87 employees of BPTP Balitbangtan Bengkulu. This study uses a quantitative approach with associative methods. While the data analysis technique used multiple linear regression. The results showed that communication had a dominant effect on morale. This confirms, that the characteristics of work in the environment BPTP Balitbangtan Bengkulu would be better if the communication aspect was considered by all parties. Even specifically, speech and how to communicate at work must be maintained, namely building a humanist communication culture (considering feelings).